The European Green Belt: Generating environmental governance – reshaping border areas - Kortelainen, Jarmo (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2010)
The article focuses on the European Green Belt (EGB), which refers to efforts to create a network of conservation areas along the borderline that used to divide Europe into the socialist and capitalist blocks. The EGB initiative attempts to link ecologically valuable areas as continuous ecological networks that cross the entire continent. The EGB is divided into three sub-regions: the Fennoscandian and Baltic Green Belt in the North and along the coastline of the Baltic Sea, the Central European Green Belt, and the South-Eastern European Green Belt. The EGB network is studied as a form of environmental governance, and its formation and furtherance are linked with the environmental governance discussion. In addition, the article aims to show that EGB governance is changing the meaning of the former Iron Curtain borders. The borders have been transnationalised since they have become parts of international networks seeking to develop borderless ecological zones. However, the EGB process maintains and reproduces the borders, as the process itself depends on the availability of suitable border areas.
Keywords: environmental governance; border areas; European Green Belt; ecological network; governance-generating network